Designing organs at the Transpecies Society: hybrid practices between cybernetics and artificial intelligence - Tatiana Afanador López; Judit Parés Padrós (Temes de Disseny)
Through narrating what happens at the Transpecies Society we will show how certain methodological criteria for designing artificial organs have arisen. What interests us here is the contrast between design inspired by cybernetics and design based on AI, in order to encourage discussions around hybrid practices.